Microorganisms and fermentation of traditional foods - Ray, Ramesh C.; Montet, Didier (Food biology series, 2015)
"The first volume in a series covering the latest information in microbiology, biotechnology, and food safety aspects, this book is divided into two parts. Part I focuses on fermentation of traditional foods and beverages, such as cereal and milk products from the Orient, Africa, Latin America, and other areas. Part two addresses fermentation biology, discussing specific topics including microbiology and biotechnology of wine and beer, lactic fermented fruits and vegetables, coffee and cocoa fermentation, probiotics, bio-valorization of food wastes, and solid state fermentation in food processing industries"-- Provided by publisher.